Inflation, Time of Debt Repayment and Firms Performance: The Evidences from Food and Beverage Companies - Anita Munir, M.Fin (Management and Leadership Study Programme, 2018)
This research is investigating the effects of macroeconomic variable on the performance of beverage industries in Indonesia which is listed in Indonesian stock exchange in last five years from 2012 until 2016. The inflation is one of the macro variables in the company that can influence the company’s value. The penal data of ten different food and beverage firms listed at Indonesia stock exchange are selected as sample for this research. The test was adopted to examine return on equity as the dependent variable that reflects to firms’ performance and inflation, time of debt repayment, as the independent variables. The data were taken by using purposive sampling method with level significant of 5%. The result of multiple linear regression analysis indicated there was a positive significant impact of debt repayment duration to return on stakeholder, meanwhile for Inflation was insignificant impact to the return on stakeholder.